A-Kinase Interacting Protein 1 Promotes Cell Invasion and Stemness via Activating HIF-1α and β-Catenin Signaling Pathways in Gastric Cancer Under Hypoxia Condition - Luo, Zhenqin; Luo, Yuhang; Xiao, Ke (Frontiers in Oncology, 2022)
Background A-Kinase interacting protein 1 (AKIP1) relates to gastric cancer growth, metastasis, and prognosis, while its regulation on gastric cancer invasion and stemness under hypoxia microenvironment is not reported. Therefore, this study aimed to explore this topic to uncover AKIP1’s role in gastric cancer under hypoxia. Methods Gastric cancer cell lines AGS and MKN45 were cultured under hypoxia condition, then transfected with AKIP1 or negative control (NC) overexpression plasmid or AKIP1 or NC knockdown plasmid. Furthermore, rescue experiments were conducted by transfecting HIF-1α or β-catenin overexpression plasmid, combined with AKIP1 or NC knockdown plasmid. Afterward, cell invasion, CD133+ cell proportion, sphere number/1,000 cells, and HIF-1α and β-catenin pathways were measured. Results The invasive cell count, CD133+ cell proportion, and sphere number/1,000 cells were enhanced in both AGS cells and MKN45 cells under hypoxia, and AKIP1 expression was also elevated. AKIP1 knockdown inhibited cell invasion, CD133+ cell proportion, sphere number/1,000 cells, HIF-1α, vascular endothelial growth factor (VEGF), β-catenin, and calcium-binding protein (CBP) expressions in AGS cells and MKN45 cells under hypoxia, while AKIP1 overexpression presented with the opposite effect. Then, in rescue experiments, HIF-1α overexpression and β-catenin overexpression both promoted cell invasion, CD133+ cell proportion, and sphere number/1,000 cells, which also attenuated the effect of AKIP1 knockdown on these functions in AGS cells and MKN45 cells. Conclusion AKIP1 promotes cell invasion and stemness via activating HIF-1α and β-catenin signaling pathways in gastric cancer under hypoxia condition.